PEMANFAATAN LIMBAH PLASTIK HDPE SEBAGAI AGREGAT PENGGANTI PADA CAMPURAN ASPHALT CONCRETE – BINDER COURSE (AC – BC) - Tajudin, Anissa Noor; Suparma, Latif Budi (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
People’s mindset regarding to waste needs to be changed: Waste materials are actually a collection of “resources and products”. With this mindset, many innovations of waste utilization will be developed. HDPE (High Density Polyethylene) is one type of plastic that is difficult to recycled and is used in large quantities for product packaging and others. This research was conducted to use HDPE plastic waste seeds as aggregate substitute in Asphalt Concrete-Binder Course (AC - BC) hotmix in order to get the solution of waste utilization. The variations of waste plastic seeds used are 0%, 25%, and 50% of the aggregate volume through sieve no. 4 and retained on the sieve No. 8 for every samples. Marshalland durability test were conducted for every variation.The results showed that the seeds could be used as aggregate substitute for fulfilling the specification from Direktorat Jendral Bina Marga.